Research Article Abstracts in Applied Linguistics and Economics: Functional Analysis of the Grammatical Subject - Ebrahimi, Seyed Foad; Chan, Swee Heng (Australian journal of linguistics, 2015)
The aims of this paper are to analyse and compare the discourse functions of grammatical subjects used in research article abstracts in the disciplines of Applied Linguistics and Economics. The data for this study consisted of 60 research article abstracts published in 2010 and 2011 in the journals of Applied Linguistics and Oxford Economic Papers. The corpus was analysed using the classification of discourse functions of grammatical subjects established by Gosden. The analysis revealed disciplinary differences concerning the discourse functions enacted by the application of the grammatical subject. These findings add to the claim that academic writing (research article abstract writing in this study) is shaped by the writer's disciplinary background with particular reference to the use of the grammatical subject as a theme in text development.